UPLB training and demonstration center for organic agriculture - Dalangin, April Mae D.M
The demand for organic produce or bio-organics is increasing worldwide. However, organic agriculture (OA) in the Philippines is still on its formative years - having adopted the Philippine Organic Agriculture Act only in 2010. Research shows that farmers and producers of bio-organics can have more than what they usually earn if they convert their systems into organic farming because the supply is still low. Meanwhile, consumers recoil from patronizing bio-organics due to its higher price than traditional produce or goods from farms that uses synthetic fertilizers. The project aims to increase market awareness on bio-organics by introducing a holistic facility that could accommodate commercial, institutional, and and agricultural-related spaces. The result is a mixed-use sustainable development in Animal Science Complex in University of the Philippines Los Baños (UPLB) that has learning, congregation, and demonstration spaces integrated with solar energy and rainwater harvesting systems in a tropically designed aesthetics. The development also integrates farming systems, creating spaces not only for learning and production, but also for recreation. With support from the community of the Center of Excellence in Agriculture (CA-UPLB), the UPLB Training and Demonstration Center for OA (UPLB-TDCOA) aims to bring a richer growth for organic agriculture in the Philippines.